Influenza A induces lactate formation to inhibit type I IFN in primary human airway epithelium - Jacob Thyrsted (Elsevier, 2021)
Summary: Pathogenic viruses induce metabolic changes in host cells to secure the availability of biomolecules and energy to propagate. Influenza A virus (IAV) and severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) both infect the human airway epithelium and are important human pathogens. The metabolic changes induced by these viruses in a physiologically relevant human model and how this affects innate immune responses to limit viral propagation are not well known. Using an ex vivo model of pseudostratified primary human airway epithelium, we here demonstrate that infection with both IAV and SARS-CoV-2 resulted in distinct metabolic changes including increases in lactate dehydrogenase A (LDHA) expression and LDHA-mediated lactate formation. Interestingly, LDHA regulated both basal and induced mitochondrial anti-viral signaling protein (MAVS)-dependent type I interferon (IFN) responses to promote IAV, but not SARS-CoV-2, replication. Our data demonstrate that LDHA and lactate promote IAV but not SARS-CoV-2 replication by inhibiting MAVS-dependent induction of type I IFN in primary human airway epithelium.